PELESTARIAN LINGKUNGAN HUTAN BERBASIS KEARIFAN LOKAL DI DESA ADAT TENGANAN PEGERINGSINGAN - Sudipa, Nyoman (UHN IGB Sugriwa Denpasar, 2024)
Local wisdom produced in the Tenganan Pegringsingan Traditional Village has been institutionalized through norms and rules which guide daily behavior for environmental sustainability and become law for the Tenganan Pegringsingan Traditional Village environment. Tenganan Pegringsingan Traditional Village encapsulates the meaning of preserving the forest environment with the mythology of Lelipi Selan Bukit, a myth that is widely known by the people of Tenganan Pegringsingan Traditional Village. Local wisdom regarding the Lelipi Selan Bukit story is a symbolic form of the existence of a forest that is sacred to the community, that the forest has a guardian so that there are hidden meanings and mysteries in the forest that are beyond human control. The power of local wisdom is wrapped in myth to control humans so that they do not damage the environment. Symbolic meaning is not a concrete meaning, but a meaning that is built on the relationship between signifier and signified based on mutual agreement. Symbolic culture is a culture that is built to strengthen relationships between humans and fellow humans, humans and the natural surroundings and humans and God the creator to build harmony with fellow humans, nature and God who is embodied through culture. Until now, the local wisdom that has been developed by the Tenganan Pegringsingan Traditional Village has been able to maintain the forest environment well. Over time, symbolic capital becomes symbolic culture, which is a culture that originates from local wisdom to strengthen relationships between humans and fellow humans, humans and the natural environment and humans and God the creator to build harmony with fellow humans, nature and God which is embodied through culture.